Tindak Tutur Ekspresif Guru dalam Pembelajaran Bahasa Indonesia Kelas X SMKN 6 Padang - Usha Putri Hardiman; Ena Noveria (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this study is to describe the form of expressive speech acts used by Indonesian teachers and describe what are the Indonesian teacher's speech strategies in the teaching and learning process in class X of SMK Negeri 6 Padang.  This type of research is qualitative research with descriptive methods. The data in this study are sentences in the form and strategy of expressive speech acts of teachers Indonesian class X of SMK Negeri 6 Padang in the teaching and learning process with the data source of one of the teachers Indonesian during the teaching and learning process. This research instrument is the author himself and is assisted by supporting instruments in the form of recording devices (cellphones) and stationery. Data collection techniques use passive pasticipation observation. The data validation technique uses the traingulation technique. The results of this study are 1) the form of teacher's expressive speech act in learning Indonesian class X SMK Negeri 6 Padang consists of expressive speech act of criticizing, expressive speech act of praise, expressive speech act of blame, and expressive speech act of apologizing, 2) Teacher speech strategy in learning Indonesian class X SMK Negeri 6 Padang consists of a strategy of speaking frankly without further ado,  The strategy of speaking frankly with positive politeness, the strategy of speaking frankly with negative politeness, and the strategy of speaking samr-vaguely.